Assessment of Antimicrobial and Enzymatic Activity using Cow based products - Sornalatha S; Saraswathi S; Ramkumar Rajendran; Esakkiammal Balakrishnan (The Bioscan, 2024)
Cow dung and cow urine have potency towards antimicrobial activity. Various extracts of cow dung possessed partial antimicrobial activity against human pathogens. Enzymes play a vital role in commercial purposes. The enzymes isolated from panchagavya and the cow products have active bio-compounds which were used for commercial purposes. In antimicrobial activity, cow dung and cow urine are used together and panchagavya alone to know the activity was studied. In this Enzyme analysis, cow products are used such as panchagavya (T1), Cow dung (T2), and cow Urine (T3) used against some human and fish pathogens. Enzymes are identified and isolated from panchagavya and cow products. In this experiment, the antibacterial activity was evaluated from cow urine, cow dung, and Panchagavya. The fermented cow product of panchagavya shows superior towards the antimicrobial activity.